SALAFI DA'WAH IN COUNTERING TERRORISM THROUGH CONTEXTUALIZATION OF JIHAD AND CULTURAL-SOCIAL ACTION: THE CASE OF SALAFI CILEUNGSI BOGOR - Adeni Adeni; Silviatul Hasanah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2021)
This article aims to analyze the da'wah of the Salafi Cileungsi of Bogor in fighting terrorism by looking at two things: their understanding of jihad and their socio-cultural action involvement. The theoretical concept used is the traditionalist Salafi (purist) concept which is different from the political Salafi and jihadi Salafi. The study uses a qualitative method, in which data are collected by interviewing, observing, and reading the community's official website. This study shows that the traditionalist Salafis of Cileungsi understand jihad in a contextual sense in which violence in the name of jihad and religion (Islam) is not justified and is inconsistent with Islamic shari'a. In addition, they display socio-cultural actions by establishing schoolhouses/educational institutions and providing moral and material assistance to people in need. They also offer jobs for the surrounding society. Contextual understanding of jihad and involvement in social action shows the humanization of Islamic teachings by Salafis. Social care is oriented towards development and peace, while terrorism is oriented towards violence and destruction. Thus, it can be said that the traditionalist Salafi of Cileungsi emphasized moderate and humanist religious ways in their preaching (da'wah).Keywords: Tradisionalist-Salafis, Cileungsi, Jihad, Social-Cultural Action, Terorrism.